Potential involvement of leptin in carcinogenesis of hepatocellular carcinoma - Wang, Xiu-Jie (World J Gastroenterol, 2004)
AIM: To investigate the potential involvement of leptin in carcinogenesis of hepatocellular carcinoma (HCC) and to elucidate the etiology, carcinogenesis and progress of HCC. METHODS: Expressions of Ob gene product, leptin and its receptor, Ob-R were investigated in 36 cases of HCC specimens and corresponding adjacent non-tumorous liver tissues with immunohistochemical staining. The effect of leptin on proliferation of Chang liver cell line and liver cancer cell line SMMC-7721 was studied with cell proliferation assay (MTT). RESULTS: Leptin expression was detected in 36 cases of adjacent non-tumorous liver tissues (36/36,100%) with moderate (++) to strong (+++) intensity; and in 72.22% (26/36) of HCC with weaker (+) intensity (P < 0.05). Thirty of 36 (83.33%) cases of adjacent non-tumorous liver tissues were positive for Ob-R, with moderate (++) to strong (+++) intensity. In HCC, 11/36 (30.56%) cases were positive, with weak (+) intensity (P < 0.05). In cell proliferation assay, leptin inhibited the proliferation of Chang liver cells. The cell survival rate was 10%-13% lower than that of the untreated cells (P > 0.05). Leptin had little effect on the proliferation of liver cancer cells (P > 0.05). CONCLUSION: High level expression and decreased or absent expression of leptin and its receptor in adjacent non-tumorous liver cells and HCC cells, inhibitory effect of leptin on the proliferation of normal Chang liver cells and no effect of leptin on proliferation of liver cancer cells, may provide new insights into the carcinogenesis and progression of human HCC. It could be assumed that leptin acting as an inhibitor and/or promoter, is involved in the process of carcinogenesis and progress of human HCC.